Potential of Cottage Industry in Azad Kashmir and the Role of Female Entrepreneurship - Faiz-ur-Rehman; Raja Nazakat Ali; Amna Aziz; Asghar Iqbal (Journal of Political Studies, 2017)
The study is aimed to explore the potential of cottage industry in Azad Jammu &Kashmir. The cottage industry holds a significant value in Azad Jammu & Kashmir where many families are engaged with it for their income generation. The indicators show that women entrepreneurship plays a significant role to boost the economic, social and cultural standard of the society. However, several problems affect the women through diverse ways due to structural inequalities. The gender relationship in household hinders women from getting their share of the economic benefits but still women continue to contribute and bear the dual workload in maintaining their status in the society. The Cross LoC Trade has opened the new advantageous opportunities for the AJ&K trading community, however; by increasing the size of the local manufacturers in Cross LoC Trade will directly benefit the home-based local industry which ultimately will improve the socio-economic status of the society.